Empowering MSMEs Globally with Digital Literacy and Financial Resilience Strategies: Memberdayakan UMKM secara Global dengan Literasi Digital dan Strategi Ketahanan Finansial - Noor, Muhammad Agil Hidayat Husni; Sriyono, Sriyono (Indonesian Journal of Law and Economics Review, 2024)
This study investigates the impact of Capital Management, Digital Literacy, Risk Management, and Record-Keeping Transaction Finance on Micro, Small, and Medium Enterprises (MSMEs) during the pandemic in Sidoarjo's Food and Beverage sector. Using a sample of 115 MSMEs, the study reveals that Capital Management, Digital Literacy, and Record-Keeping Transaction Finance positively influence MSME finance performance, while Risk Management shows no significant impact. The findings underscore the importance of effective financial strategies and digital literacy in bolstering MSME resilience during challenging times, offering practical insights for policymakers and stakeholders aiming to support MSME growth and sustainability. Highlight: Financial resilience through strategic management empowers MSMEs during crises. Digital literacy fuels MSME growth, enhancing online marketing and engagement. Understanding risk management is vital for MSME sustainability and success. Keyword: MSMEs, Capital Management, Digital Literacy, Risk Management, Pandemic